Growth rates of valuable tree species in secondary tropical montane cloud forests in Mexico: influence of tree size, crown position and competition - Mendoza-Hernández, Magdaleno; Gerez-Fernández, Patricia; Purata-Velarde, Silvia; Toledo-Aceves, Tarin (Instituto de Ecología, A.C., 2019)
Tropical montane cloud forests (TMCF) are under severe threat from deforestation, fragmentation and degradation. Several tree species are harvested and commercialized by local communities through unplanned selective logging. Lack of information regarding the growth rates of the most economically valuable timber species hampers the design of effective sustainable management schemes for TMCF. The objective of this study was to determine the diameter growth rates and evaluate the influence of tree size, crown class and neighbouring tree basal area on the growth of common and valuable TMCF timber species. Annual diameter growth was measured during two years in 60 trees (10 to 45 cm in diameter at breast height; dbh) each of Alnus acuminata, Liquidambar styraciflua and Quercus xalapensis, located in two unmanaged secondary TMCF sites in Veracruz, Mexico. High diameter growth rates (centimeter per year [cm yr-1]; mean ± SE) were recorded in the three species; the highest was recorded in A. acuminata (1.62 cm yr-1 ± 0.08 cm yr-1), followed by Q. xalapensis (0.91 cm yr-1 ± 0.07 cm yr-1) and L. styraciflua (0.71 cm yr-1 ± 0.08 cm yr-1). Diameter growth rate was inversely related to the basal area of the neighbouring trees, indicating a negative effect of competition in the three species. Dominant trees had higher growth rates than supressed trees in the three species. The high growth rates recorded in forests with no previous management and the negative effect of basal area of neighbouring trees support the potential for silvicultural management in secondary TMCF.